EARLY CRETACEOUS ALKALINE BASIC ROCKS AND CARBONACEOUS METASOMATITES OF THE PRIMOR'E REGION - Baskina V.A.; Tomson I.N.; Arakelyants M.M.; Polyakova O.P. (My University, 2004)
This article discusses the isotopic dates for the Albian alkaline basic rocks (116-104 Ma) in the Pribrezhnaya structural zone of the Primor'e region and investigated their mineral compositions. The graphite-ilmenite metasomatites and plume-related alkaline basalts are characterized by similar features of the structural position, age, and geochemical properties, indicating their genetic relationship. The graphite-ilmenite metasomatites contain abundant nanoinclusions of several rare and noble metals. These metasomatites are considered products of the abyssal reduced fluids. Reactivation of the alkaline basaltic sources with the formation of potassic metamagmatites and metasomatites took place in the Paleocene, i.e., prior to the deposition of the commercial-scale datolite and base metal ores in the Dal'negorsk region.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая